2020
DOI: 10.1016/j.molcel.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Three Distinct Mechanisms Supporting RNA-Driven DNA Repair and Modification Reveals Major Role of DNA Polymerase ζ

Abstract: Highlights d DNA polymerase z promotes RNA-templated DNA repair and modification d cDNA-, unlike RNA-templated DNA repair, requires endclipping function d RNA-mediated DNA modification proceeds in the absence of recombination genes d Mismatch repair facilitates accurate repair with template RNA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 81 publications
2
32
0
Order By: Relevance
“…Although the mechanistic details remain to be fleshed out, it has been proposed that the RNAbinding activity of RPA induces a conformational change in RAD52 that favors strand exchange between DSB ends and homologous RNA templates (Keskin et al, 2014;Mazina et al, 2017). In budding yeast, translesion DNA polymerase ζ is able to reverse transcribe RNA and use it as a repair template at DSB sites (Meers et al, 2020). It will be important to test whether human Pol ζ or other human DNA polymerases similarly promote reverse transcription to fill in gaps during RNA-templated DNA repair.…”
Section: Rna-binding Protein-rna Interactions Are Central To Double-strand Break Signaling and Repairmentioning
confidence: 99%
“…Although the mechanistic details remain to be fleshed out, it has been proposed that the RNAbinding activity of RPA induces a conformational change in RAD52 that favors strand exchange between DSB ends and homologous RNA templates (Keskin et al, 2014;Mazina et al, 2017). In budding yeast, translesion DNA polymerase ζ is able to reverse transcribe RNA and use it as a repair template at DSB sites (Meers et al, 2020). It will be important to test whether human Pol ζ or other human DNA polymerases similarly promote reverse transcription to fill in gaps during RNA-templated DNA repair.…”
Section: Rna-binding Protein-rna Interactions Are Central To Double-strand Break Signaling and Repairmentioning
confidence: 99%
“…Given that ribonucleotides are the most frequently occurring nucleotide lesion in genomic DNA that arrest replicative Pols and cause DNA breaks ( 19 , 20 ), we also envisaged that Polθ would tolerate template ribonucleotides during its DNA repair activities and thus promote RNA-templated DNA repair synthesis (RNA-DNA repair). Although RNA-DNA repair mechanisms have been demonstrated in genetically engineered yeast cells ( 21 , 22 ), they remain obscure in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…HDR may be directed by an RNA template, which has been discovered and mechanistically explored in yeast [ 123 ]. A recent study showed that RNA-templated recombination in postmitotic neurons occurred with the involvement of RAD52 and that the affinity of RAD52 to RNA might exceed that to DNA [ 124 ].…”
Section: Discussionmentioning
confidence: 99%